Flood modeling of dam break with consideration of climate change - Sammen, Saad Shauket (2017)
In this study, the failure of cascade dams in a tropical region is simulated using mathematical models. The simulation is considering the climate change impact. Three cascade dams for hydropower generation on the Perak River were taken as case studies. The three dams are of different designs, ages and heights which make a unique complex dam system. The proposed models were categorized as dam breach parameters model, hydrological model and hydrodynamic models. The dam breach parameters model is based on generalized regression neural network, GRNN while the hydrological model and hydrodynamic models are Mike 11 (NAM sub-model), 1-D Mike 11 and 2-D Mike 21. The GRNN was used to estimate the dam breach parameters. Dam breach parameters such as breach width, breach height and breach formation time are the key variables to estimate the peak discharge during dam break. Because of the high nonlinear relationships in dam breach parameters and their variation with time, the estimation of these parameters is considered very complex. The training and testing of GRNN models were conducted using records of more than 140 failed dams around the world in order to estimate dam breach parameters. The results obtained from GRNN models for dam breach parameters were compared with the results obtained from the existing methods. The computed value of Mean Relative Error, MRE for GRNN models were found to be ranged from 0.11 to 0.17 while values of MRE for the existing methods were founded to be ranged from 0.15 to 0.33 for dam breach width estimation. For dam failure time estimation, the values of MRE were found to be ranged from 0.08 to 0.16 for GRNN model results and from 0.34 to 0.57 for the existing methods’ results. In this study, the hydrological model was developed using Mike 11 (NAM sub-model). The Mike 11 (NAM sub-model) is a lumped conceptual model which forms part of the rainfall-runoff (RR) module of the MIKE 11 river modeling system. Time series of rainfall, evaporation and streamflow data for the Temenggor catchment were used to calibrate and validate the hydrological model for the Temenggor dam (the largest dam in the studied dam system). The developed model was applied to predict the probable maximum flood, PMF. Also, the impact of climate change on value of PMF was considered by estimation the PMF value for two future period which include future 1 period (2031 – 2045) and future 2 period (2061 – 2075). The values of PMF were found to be 2887.53 m3/s, 4299.43 m3/s and 6427.89 m3/s for periods (2001 – 2015), (2031 – 2045) and (2061 – 2075) respectively. The 1-D Mike 11 hydrodynamic model was calibrated and validated using recorded water levels and streamflow for Perak river. Then the model was applied to determine simulated maximum peak outflow from Temenggor, Bersia and Kenering dams for four scenarios. By using the PMF for the period from 2061 to 2075, the maximum peak outflow for the above dams was found to be 272602.59 m3/s, 217984.96 m3/s and 184922.01 m3/s respectively. Also, flood routing for Perak river, flood hydrograph and water level hydrograph at different sections were simulated. The 2 – D Mike 21 hydrodynamic model was used to routing the flood that will result from the simulated maximum peak outflow from Temenggor, Bersia and Kenering dam failures for four scenarios. Flood arrival time, maximum water depth and time to maximum water depth were estimated for different selected villages downstream of the three dams above. Additional, the flood inundation maps were found for different scenarios.